The evolution of child-related gender inequality in Germany and the role of family policies, 1960-2018 - Ulrich Glogowsky; Emanuel Hansen; Dominik Sachs; Holger Lüthen (Johannes Kepler University of Linz, Department of Economics, 2024)
Using German administrative data from the 1960s onward, this paper (i) examines the long-term evolution of child-related gender inequality in earnings and (ii) assesses the impact of family policies on this inequality. We present three sets of findings. First, child penalties (i.e., the percentage of potential earnings lost due to children) have strongly increased over the last decades. Mothers who had their first child in the 1960s faced much smaller penalties than those who gave birth in the 2000s. Second, we decompose overall gender inequality into childrelated and child-unrelated components. Over our sample period, the fraction of overall inequality attributed to children rose from 14% to 64%. This trend not only resulted from the growing child penalties but also from rising potential earnings of mothers. Intuitively, in later decades, mothers had more income to lose from child-related career breaks. Third, we investigate the role of policy decisions in this rise in child penalties. Parental leave expansions between 1979 and 1992 amplified child penalties and contributed nearly one-third to the increase in child-related gender inequality. Instead, a parental benefit reform in 2007 mitigated further increases. While the third set of results highlights the role of family policies, the first two imply that sidelining mothers becomes increasingly costly over time.
Keywords: 330